Physicochemical and Morphological Properties of Extruded Adlay (Coix lachryma-jobi L) Flour. (5th December 2019) - Zhang, Gaopeng; Ding, Yangyue; Ni, Chunlei; Ban, Qingfeng; Xu, Li; Guo, Liandong; Cheng, Jianjun
Abstract : The effects of extrusion treatment on the structure and properties of adlay (Job's tears) were investigated. Adlay flour was extruded through a twin-screw extruder with different parameters, including barrel temperature (80–160°C), moisture content (19–27%), and screw speed (170–330 rpm). The results showed that although the expansion index increased with increasing temperature, an increase in moisture content significantly decreased the EI (p < 0.05 ). Extrusion improved the water solubility index and water absorption index of adlay flour (p < 0.05 ). Furthermore, analysis of the gelating properties revealed that the structure and function of adlay flour had radically changed. After extrusion, the viscosity of the adlay flour decreased (peak viscosity decreased by more than 1000 cP), and its fluidity increased. The rheological data were modeled by the Herschel–Bulkley model. X-ray diffraction experiments showed that extrusion contributed to a decrease in relative crystallinity. Scanning electron microscopy revealed that extrusion damaged the basic structure of adlay flour, causing holes and pits on the extrudate surface. Compared to the native adlay flour, the extrusion resulted in significantly changing the pasting, gelating, thermal, rheological, and morphological properties of adlay flour. In conclusion, the extrusion can alter adlay characteristics, but it is necessary to choose appropriate conditions to attain the desired properties.